The single window concept in international trade, transport and seaports - Tijan, Edvard (Array, 2019)
This paper presents a review of electronic data exchange and Single Window concept in international trade, transport and seaports. The theoretic framework of international trade, trade facilitation, Single Window, transport sector, maritime transport and seaports is provided, as well as the definition of electronic data exchange and standards for data exchange. The time and cost (excluding tariffs) associated with documentary compliance procedure (exporting and importing a shipment of goods) are shown in order to better understand the complexity and the importance of simplifying administrative processes. The importance of stakeholder connectivity in the transport sector (with special emphasis on seaports) is demonstrated, and factors which affect the successful electronic data exchange in seaports are shown. The advantages of smoother electronic data exchange are provided through the analysis of several Single Window examples, which present regional best practices.